The Implication of Tillage Practices and Decapitation Techniques on the Growth and Biomass Yield of Fluted Pumpkin - Tom, C. N.; Edet, J. A.; Erokare, T. E.; Igbozulike, A. O.; Ugwu, E. C.; Orji, F. N.; Udenze, N. F. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2024)
The implication of tillage practices and decapitation techniques on the growth and biomass yield of fluted pumpkin (Telfairia occidentalis) cultivated in an inland swamp land in the dry season was studied. The treatments considered on decapitation were: (A) the control (intact/un-decapitated plants), (B) removal of half the total number of branches on the plant at time of decapitation, (C) removal of all lateral branches and leaves at time of decapitation, (D) removal of all the leaves on the plant at time of decapitation and (E) cutting off half of the entire shoot system. While the treatments considered on tillage practices were: (i) Bed tillage (ii) Ridge tillage (iii) Flat (No tillage). Therefore, the total treatment combinations were fifteen. After the imposition of decapitation, data were collected on growth and yield parameters of the newly developed foliage. The parameters were number of leaves, plant height, total number of new branches, leaf length and breadth, the fresh and dry weight of root, leaves, and shoot biomass. The decapitation (harvesting) techniques and tillage practices adopted in this study affected biomass re-growth and development of fluted pumpkin (Telfaira occidentalis). Removal of half number of branches on bed tillage practice gives the best performance, when compared with the intact (control) plant and other treatments.